Thermal assisted self-organization of calcium carbonate - Gan Zhang (Nature Portfolio, 2018)
Self-organization of multi-textured mineral architectures is challenging. Here, the authors control the growth temperature of silica carbonate biomorphs and demonstrated the structure is not limited to orthorhombic carbonates and open a route for creating complex self-organised silica and chalk materials.